Conduction system pacing in difficult cardiac anatomies: Systematic approach with the 3D electroanatomic mapping guide - Lina Marcantoni; Marco Centioni; Gianni Pastore; Federico Aneris; Enrico Baracca; Francesco Zanon (Indian Pacing and Electrophysiology Journal, 2023)
Introduction: Restoring physiological cardiac electrical activity in patients with conduction disease can be crucial for the survival and quality of life. Conduction system pacing (CSP) is a valuable option, although it is limited by technical challenges in difficult anatomies. 3D electroanatomical mapping (3D-EAM) can support CSP ensuring high electro-anatomical precision and low fluoroscopy. Objectives: We evaluated the feasibility and effectiveness of a systematic 3D-EAM use to guide CSP in difficult anatomical scenarios (highly dilated atria, congenital cardiomyopathies, failed biventricular implants (BiV) and pacing-induced cardiomyopathy (PICM)). Methods: Forty-three consecutive patients (27 males, 75 ± 10 years old) with standard pacing indications and difficult anatomical scenarios were included. The right atrium, His cloud, and atrio-ventricular septum were reconstructed by 3D-EAM. The His bundle (HB) was the initial target, while left bundle branch area pacing (LBBAP) was aimed at in case of unsatisfactory parameters, sub-optimally paced QRS, or impossibility of reaching the HB. Results: CSP was successful in 37 (86%) patients (15 HBP; 22 LBBAP). Mean mapping, fluoroscopy, and procedural times were 18 ± 7 min, 7 ± 5 min, 98 ± 47 min, respectively. The mean pacing threshold, R wave sensing, and pacing impedance of CSP lead were 1.2 ± 0.5V@0.5ms, 11.4 ± 6.2 mV, 736 ± 306 Ω, respectively. Baseline and paced QRS were 139 ± 38 ms and 114 ± 23 ms, respectively. No procedural complications were observed. Conclusions: 3D-EAM allowed the accurate definition of the His cloud and high ventricular septum and effectively guided CSP. It facilitated CSP in complex anatomies, with a procedural success rate of 86%. The results were satisfactory and reproducible, with acceptable fluoroscopy and procedural times.